A two-step procedure for the selection of innovative high temperature heat transfer fluids in solar tower power plants. (November 2021) - Manzolini, Giampaolo; Lucca, Gaia; Binotti, Marco; Lozza, Giovanni
Abstract: This work compares with a two-step procedure the performance of different Heat Transfer Fluids (HTF) for high temperature receiver applications (up to 715 °C) in advanced Solar Tower (ST) plants. The most promising molten salts and liquid metals are initially selected and ranked according to their performance, estimated with different Figures of Merit (FoM) available in literature or newly defined. For the best performing fluids, different hydraulic configurations and tube diameters at fixed receiver size are tested. The optimized external tubular receiver configuration for each HTF is then implemented in a ST plant and its performance is assessed through a detailed techno-economic analysis, considering the use of a direct thermal energy storage system and of a sCO2 based power cycle. As a second step, the yearly electricity yield and the LCOE are evaluated for two different sites. Results show NaCl–MgCl2 as the best option for the considered type of plant with a LCOE of 151 $/MWh, which is anyhow 10% higher than the reference Solar Salts case. Highlights: Potential heat transfer fluids for solar tower application at 715°C are identified. A multi-criteria approach based on Figure of Merits is applied for HTF selection. For each HTF different receiver circuitry and tubes size are evaluated. Solar Multiple and Storage Size are optimized for each HTF minimizing LCOE. The HTF ranking based on LCOE is compared with the multi-criteria ranking.